Draft letter from Roger Casement to Sir Gerald Spicer providing an account of the amount of rubber shipped from Iquitos in September and how much of it was from the Putumayo, and also providing an extract from a letter between "Senor Tizon" and Hal Gielgud, - Casement, Roger, 1864-1916 (1912)
Casement furthermore discusses the Franciscan Mission to the Putumayo.